Dual-catalytic CuTPP/TiO2 nanoparticles for surface catalysis engineering of cardiovascular materials. (15th December 2022) - Liu, Luying; Liu, Peng; Yang, Youhe; Dai, Sheng; Wang, Zhixing; Zhao, Ansha; Huang, Nan; Chen, Jiang; Yang, Ping
Abstract: Endowing materials with catalytic activities analogous to those of the natural endothelium to thus enhance their biological performance has become an option for constructing advanced blood-contact materials. The electron transfer between Cu2+ and Cu+ in the porphyrin center can catalyze the reaction of GSH and GSNO to generate NO, and this electron transfer can also catalyze the decomposition of ROS. Based on this, we created a dual-catalytic surface possessing NO-generating and ROS-scavenging activities to better mimic the versatile catalytic abilities of the endothelium. Copper tetraphenylporphyrin/titanium dioxide nanoparticles (CuTPP/TiO2 -NPs) exhibiting excellent NO-generating and ROS-scavenging activities were synthesized and immobilized on the material surface to form a dual-catalytic film (CuTPP/TiO2 -film) with the help of the catechol chemistry technique. Unlike most single catalytic surfaces, the dual-catalytic CuTPP/TiO2 -film effectively regulated the microenvironment surrounding the implanted device by releasing NO signaling molecules and scavenging harmful ROS. This dual-catalytic film exhibited excellent biosafety and biocompatibility with anti-thrombosis, vascular wall cells (ECs and SMCs) modulation, and anti-inflammatory properties. We envision that this dual-catalytic endothelial bionic strategy may provide a promising solution to the clinical problems plaguing blood-contact devices and provide a novel basis for the further development of surface catalytic-engineered biomaterials. Graphical abstract: Image 1